Factors Affecting the Curriculum Implementation in Teaching of Chemistry in Senior Secondary School in Onitsha Education Zone in Anambra State - Okongwu, Dozie John (Fakultas Pendidikan Ilmu Keguruan, Universitas Pahlawan Tuanku Tambusai, 2025)
The study investigated the factors affecting the curriculum implementation in teaching of chemistry in senior secondary school in Onitsha education zone in Anambra state. The study adopted the descriptive survey research design. Five research questions guided the study. The population of the study comprised all the 98 chemistry teachers in Onitsha Education Zone, Anambra State. A sample of 98 chemistry teachers was used for the study. The instrument for data collection was a structured questionnaire developed by the researchers which was titled ‘Questionnaire on factors affecting curriculum implementation in teaching of Chemistry (QFACITC). The instrument was validated by three experts and the reliability of the instrument was obtained using Cronbach Alpha reliability which gave a reliability index of 0.85. Data were collected were analyzed using mean and standard deviation to answer the research questions. The findings of the study revealed the following: that teachers perceive the effectiveness of the current chemistry curriculum effective in meeting educational objectives and student learning needs, the primary challenges faced by teachers in implementing the chemistry curriculum effectively in the senior secondary school, as found by the study include; inadequate laboratory equipment, insufficient textbooks and educational materials limit teaching effectiveness among others, cultural and societal factors influence the implementation of the chemistry curriculum, technology is effective in the delivery and enhancement of the chemistry curriculum implementation, adequate resource allocation, digital resources, clear policy guidelines, real-world applications, periodic curriculum review are strategies that can be implemented to overcome the challenges affecting effective curriculum implementation in chemistry education in secondary schools. Based on the findings of the study, the following recommendation were made: provision of laboratory facilities should be by a combined effort of the government, Parent Teachers’ Association and other education stakeholders; Chemistry teachers and students should improvise instructional materials especially those that involve the use of local materials; philanthropists should invest in the education needs of their community especially in the area of instructional material provision as well as fund assistance; Chemistry teachers should be involved in decision-making and the planning of the Chemistry curriculum.